PENGEMBANGAN KOMERSIALISASI PERTANIAN MELALUI KONSEP INTEGRASI INDUSTRIALISASI PERTANIAN - Arie Saputra; Fitriadi Fitriadi; Sofiyanurriyanti Sofiyanurriyanti; Nissa Prasanti; Adib Adib; Muzakir Muzakir (Universitas Teuku Umar, 2022)
Community service activities (CSA) are a medium for delivering science and technology to the public. The implementation of this service is carried out by Lecturers of the Industrial Engineering Study Program, Faculty of Engineering, Teuku Umar University. The implementation of this PKM with the theme of Commercialization of Agriculture is located in the Gampong Leukeun area, Samatiga District, West Aceh Regency, Aceh Province, Indonesia. The purpose of this Community Service is to give an overview to the Gampong Community about the importance of Agricultural Commercialization and as an initial effort to increase the commercial capacity of agricultural products by providing guidance and assistance. After the service is carried out, it is hoped that village apparatus and the community can understand and be able to apply it in Gampong Leukeun. Efforts are needed to narrow the gap so that the level of inequality in community groups in the village can be met, such as productivity gaps, digital inequality, data and information agriculture, Digital Agriculture and Millennials. for example through mentoring, intensive counseling and capacity building in farmer groups.